2020
DOI: 10.1007/s11440-020-01063-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SPH boundary approaches in simulating frictional soil–structure interaction

Abstract: Two boundary algorithms in the framework of 3D smoothed particle hydrodynamics (SPH) method are proposed. The algorithms are capable of accounting for the friction and energy dissipation at elastic-plastic contacts between SPH particles and a solid boundary. Utilizing the proposed boundary algorithms, the accuracy of different methods to calculate the interaction force between SPH particles and a boundary surface is investigated. The effect of SPH artificial viscosity on the oscillation and accuracy of the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Consequently, in the experiments, Lube et al observed that the flow process and final deposit are independent from the surface friction. 73 Similar observation can be found in Sheikh et al 46 and the conclusion of effective frictional angle conducted from del Castillo et al 56 is naturally included here.…”
Section: The Influence Of the Surface Frictionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consequently, in the experiments, Lube et al observed that the flow process and final deposit are independent from the surface friction. 73 Similar observation can be found in Sheikh et al 46 and the conclusion of effective frictional angle conducted from del Castillo et al 56 is naturally included here.…”
Section: The Influence Of the Surface Frictionsupporting
confidence: 88%
“…The undisturbed regime will be flattened with the decreasing 𝜇 values, and the spreading regime is a thin thickness and formed by spreading particles. The comprehensive discussions on these different regimes can be found in Sheikh et al 46 Clearly, it is found that in the simulation with lesser surface friction, the radius of the spreading regime will be more significant, as shown in Figure 8. When the frictional coefficient is too small, all the materials will flow in the collapse process, as the resistance from the boundary is insufficient.…”
Section: The Influence Of the Surface Frictionmentioning
confidence: 89%
See 2 more Smart Citations
“…SPH has been used successfully for the modelling of other granular materials such as sand, gravels and soils (Salehizadeh and Shafiei, 2019;Yang et al, 2020;Sheikh et al, 2020). In the context of mesoscale and larger sea-ice modelling, Gutfraind and Savage (1997) initiated the SPH study of sea-ice dynamics using a VP rheology based on a Mohr-Coulomb failure criterion.…”
Section: Introductionmentioning
confidence: 99%